Conversion of a Mono‐ and Diacylglycerol Lipase into a Triacylglycerol Lipase by Protein Engineering. Issue 10 (29th May 2015) - Lan, Dongming; Popowicz, Grzegorz Maria; Pavlidis, Ioannis V.; Zhou, Pengfei; Bornscheuer, Uwe T.; Wang, Yonghua
Abstract Despite the fact that most lipases are believed to be active against triacylglycerides, there is a small group of lipases that are active only on mono‐ and diacylglycerides. The reason for this difference in substrate scope is not clear. We tried to identify the reasons for this in the lipase from Malassezia globosa. By protein engineering, and with only one mutation, we managed to convert this enzyme into a typical triacylglycerol lipase (the wild‐type lipase does not accept triacylglycerides). The variant Q282L accepts a broad spectrum of triacylglycerides, although the catalytic behavior is altered to some extent. From in silico analysis it seems that specific hydrophobic interactions are key to the altered substrate specificity.